Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1099/jmm.0.001276
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric bacterial meningitis in the USA: outcomes and healthcare resource utilization of nosocomial versus community-acquired infection

Abstract: Introduction. Paediatric bacterial meningitis remains a costly disease, both financially and clinically. Hypothesis/Gap Statement. Previous epidemiological and cost studies of bacterial meningitis (BM) have largely focused on adult populations or single pathogens. There have been few recent, large-scale studies of pediatric BM in the USA. Aim. We examined healthcare resource utilization (HCRU) and associated morbidity and mortality of communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In general, patients with bacterial meningitis were dominated by men (55.7%), both in community-acquired and nosocomial cases [16]. Children aged less than 2 years are more susceptible to bacterial meningitis than older children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, patients with bacterial meningitis were dominated by men (55.7%), both in community-acquired and nosocomial cases [16]. Children aged less than 2 years are more susceptible to bacterial meningitis than older children.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure is quite common, especially for cases of hydrocephalus. Previous studies have stated that the most common bacteria causing meningitis in the use of a VP shunt is Staphylococcus bacteria [16]. Despite advances in surgical techniques and infection control, infections associated with VP shunt placement still range from 5 to 18% and are mostly caused by gram-positive bacteria (59%) [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 39 Systemic complications such as severe sepsis and/or multiple organ dysfunction syndrome (MODS) occurred in 34.2% of CABM cases in this study, which was higher than previous USA studies. 40 CABM cases who developed systemic complications had complex clinical presentations and some patients had significantly higher rates of sequelae. Therefore, under the premise of effective anti-infection, clinicians must pay attention to monitor the changes of the condition, timely detection of complications, and active management, which is expected to reduce the disability and death rate of children’s CABM, and thus improve the prognosis of children.…”
Section: Discussionmentioning
confidence: 99%
“…Acute bacterial meningitis can have severe complications with long-term neurological sequelae resulting in disability even in high-income countries (HICs) with appropriate antibiotic therapy and vaccine availability [ 26 ]. For example, a recent study in the United States on paediatric bacterial meningitis demonstrated a 45.9% complication rate at 30 days for community-acquired bacterial meningitis, with hydrocephalus (20.8%), intracranial abscess (8.8%) and cerebral oedema (8.1%) being the most common short-term neurological sequelae [ 27 ].…”
Section: Neurological Sequelaementioning
confidence: 99%